Analisis Perbaikan Defect Slag Inclusion Menggunakan SPC dan FMEA pada Jacket Structure di PT. McDermott - Novia Nur Rhamadhan; Hery Irwan (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Welding operations in jacket structure fabrication require strict quality control because defects may reduce joint integrity and increase rework. This study aims to analyze slag inclusion defects, evaluate process stability, identify root causes, and determine improvement priorities in the flux-cored arc welding process at PT McDermott. A quantitative approach was applied using Statistical Process Control (SPC), cause-and-effect diagram, and Failure Mode and Effects Analysis (FMEA). Data were collected from Ultrasonic Testing (UT) and Magnetic Particle Inspection (MPI) covering 340 welded joints from October 2025 to April 2026. The results show that 23 joints were defective, with 12 cases (52.17%) identified as slag inclusion. Verification confirms that all welding parameters comply with the Welding Procedure Specification (WPS). The p-chart analysis resulted in an average defect proportion of 0.0353. One subgroup on February 25, 2026 recorded a proportion of 0.1600, exceeding the upper control limit of 0.1460, indicating that the process is not fully statistically controlled. FMEA identified inadequate interpass slag cleaning as the highest-risk cause with an RPN of 224. After improvements, the total RPN decreased from 1,288 to 301, representing a 76.63% reduction. These findings indicate that the integration of SPC and FMEA effectively identifies process variation and reduces operational risk.